resolva -5[(-5)2-(-2-raiz quadrada de 9).5]
ednaelli:
Esclareça melhor
Soluções para a tarefa
Respondido por
0
-5[(-5)2-(-2-√9).5] =
-5[(-5)2-(-2-3).5] =
-5[(-5)2-(-5).5] =
-5[(-5)2-(-25)] =
-5[(-5)2+25] =
-5[-10 + 25] =
-5[ 15 ] =
-75
-5[(-5)2-(-2-3).5] =
-5[(-5)2-(-5).5] =
-5[(-5)2-(-25)] =
-5[(-5)2+25] =
-5[-10 + 25] =
-5[ 15 ] =
-75
Perguntas interessantes
Matemática,
11 meses atrás
Filosofia,
11 meses atrás
Biologia,
11 meses atrás
Biologia,
1 ano atrás
Biologia,
1 ano atrás
Química,
1 ano atrás
Física,
1 ano atrás
Matemática,
1 ano atrás